Institutional quality and foreign aid - Marcus Drometer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
This paper investigates the impact of foreign aid on the quality of institutions in recipient countries. Our identification strategy exploits the shift in US foreign policy due the attacks on the World Trade Center on September 11th, 2001 as a quasi-natural experiment. The associated change in strategic importance of certain countries is resembled in the pattern of foreign aid flows. We estimate the impact of US foreign aid on different measures of institutional quality in a cross-country panel data set of developing countries. Our results indicate that foreign aid impacts different dimension of a country's institutions: When focusing on the rule of law aid seems to have a detrimental effect. However, the tax burden imposed on the citizens in recipient countries seems to be reduced by aid payments. When looking at the general level of democratization, we cannot find any conclusive results.
Keywords: H11; D72; F22; 330; Foreign aid; institutional quality; natural experiment